2016
DOI: 10.1016/j.jprot.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics of uropathogenic Escherichia coli during growth in human urine identify UCA-like (UCL) fimbriae as an adherence factor involved in biofilm formation and binding to uroepithelial cells

Abstract: Uropathogenic Escherichia coli (UPEC) are the primary cause of urinary tract infection (UTI) in humans. For the successful colonisation of the human urinary tract, UPEC employ a diverse collection of secreted or surface-exposed virulence factors including toxins, iron acquisition systems and adhesins. In this study, a comparative proteomic approach was utilised to define the UPEC pan and core surface proteome following growth in pooled human urine. Identified proteins were investigated for subcellular origin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 75 publications
3
49
1
Order By: Relevance
“…One could speculate that, in our study, the biocides at these subinhibitory concentrations deplete the bacteria of nitrogen. The DppA protein (periplasmic dipeptide transport protein) was found to be expressed on the surface of E. coli CFT073 and four other reference UPEC strains during in vitro growth in human urine, identified by mass spectrometric analysis of EDTA heat-induced outer membrane vesicles (OMVs) [59].…”
Section: Discussionmentioning
confidence: 99%
“…One could speculate that, in our study, the biocides at these subinhibitory concentrations deplete the bacteria of nitrogen. The DppA protein (periplasmic dipeptide transport protein) was found to be expressed on the surface of E. coli CFT073 and four other reference UPEC strains during in vitro growth in human urine, identified by mass spectrometric analysis of EDTA heat-induced outer membrane vesicles (OMVs) [59].…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution liquid chromatograph-mass spectrometry/mass spectrometry (LC-MS/MS)-based technology has been applied to identify and characterize the surface proteome of UPEC isolates and of strains grown in human urine (Wurpel et al, 2015 , 2016 ). These studies identified several expressed proteins highly conserved among different strains, thus representing the core surface proteome of UPEC.…”
Section: Uropathogenic Escherichia Coli and Its VImentioning
confidence: 99%
“…Urinary tract infection (UTI) is one of the most prevalent diseases worldwide, affecting both community and hospitalized subjects, resulting in impairment of the patients' life quality (Terpstra and Geerlings, 2016 ; Wurpel et al, 2016 ). Several factors, such as surgical manipulation, diabetes, previous hospitalizations, and catheterization, are related to a higher risk for developing this disease (Saltoglu et al, 2015 ; Redder et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%